Penerapan Inovasi Digital untuk Meningkatkan Daya Saing UMKM di Desa Cijayanti - Palahudin; Titiek Tjahja Andari; Andy Lesmana; Indra; Wahyu Pratama; Novy Ramadhina; Padila Nurhikmah; Arif Luqman Ibrahim (LPPM UNINUS, 2025)
This community service program aims to improve the understanding and skills of micro, small, and medium enterprises (MSMEs) in Cijayanti Village through the application of digital innovation. The program was carried out through training sessions, workshops, and practical mentoring, focusing on the use of social media, e-commerce platforms, and simple applications to support marketing and business management. The results showed an increase in participants’ knowledge and basic skills in creating digital promotional content, managing social media accounts, and starting the use of online stores. In addition, the program fostered motivation among MSME actors to develop technology-based marketing strategies. Although the long-term impact cannot yet be measured due to limited monitoring time, this activity serves as an initial foundation for MSMEs in Cijayanti Village to enhance their competitiveness through the adoption of digital innovation.